2007
DOI: 10.1016/j.jcrs.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stromal hydration of clear corneal incisions: Quantifying ingress of trypan blue into the anterior chamber after phacoemulsification

Abstract: Stromal hydration of clear corneal incisions reduced ingress into the anterior chamber of the trypan blue instilled on the ocular surface. Clinically, these findings may have a beneficial effect in reducing the risk for postoperative endophthalmitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 16 publications
0
31
1
Order By: Relevance
“…The main and the paracentesis incisions were hydrated. 36 If an intraoperative complication occurred, the surgeon implanted an alternative IOL in the sulcus and the patient was excluded from the study.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The main and the paracentesis incisions were hydrated. 36 If an intraoperative complication occurred, the surgeon implanted an alternative IOL in the sulcus and the patient was excluded from the study.…”
Section: Surgical Techniquementioning
confidence: 99%
“…[9][10][11][12] Controlled laboratory models using India ink 13,14 have shown penetration of bacterial-sized particles into the sutureless CCI stromal tunnel and into the anterior chamber. Other studies [15][16][17] found penetration of blood, trypan blue, and antibiotic ointment into the anterior chamber during the immediate postoperative period when sutureless CCIs were used. One proposed mechanism to explain this phenomenon is that during the early postoperative period, extraocular fluid and particles may gain access to the anterior chamber through a defective sutureless incision, especially when the intraocular pressure (IOP) is low and endothelial gaping and loss of coaptation are more common.…”
mentioning
confidence: 99%
“…However, literature suggests that the stromal edema caused by hydrosealing lasts as little as 15 minutes in operated eyes and thus is considered a transient solution (15,17) . Chee et al performed intraoperative stromal hydration in an attempt to seal leaking incisions.…”
Section: Discussionmentioning
confidence: 99%